Hank the Cowdog: The Almost Last Roundup - Book 65 - Erickson, John R. 1943-; Holmes, Gerald L. (Perryton, TX : Maverick Books, Inc., 2015)
Nobody on the ranch has seen a drought like the one this summer, ponds have dried up, the creek is down, and the cows are kicking up dust. Then there is a prairie fire. There is a desperate need for rain, and Pete the Barncat is trying to ruin Loper's birthday.
Keywords: Hank the Cowdog (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Ranch life -- Juvenile fiction; Humorous Stories; Hank the Cowdog (Fictitious character) -- Fiction; Dogs -- Fiction; Ranch life -- Fiction; Western stories